Tristemma hirtum and Five Other Cameroonian Edible Plants with Weak or No Antibacterial Effects Modulate the Activities of Antibiotics against Gram-Negative Multidrug-Resistant Phenotypes - Gaëlle S. Nguenang; Armelle T. Mbaveng; Aimé G. Fankam; Hermione T. Manekeng; Paul Nayim; Brice E. N. Wamba; Victor Kuete (The Scientific World Journal)
In order to contribute to the fight against infectious diseases, the in vitro antibacterial activity and the antibiotic-potentiating effects of Tristemma hirtum and five other Cameroonian edible plants have been evaluated against Gram-negative multidrug-resistant (MDR) phenotypes. The microdilution method was used to evaluate the bacterial susceptibility of the extracts and their combination to common antibiotics. The phytochemical screening of the extracts was carried out according to standard methods. Phytochemical analysis of the extracts revealed the presence of alkaloids, triterpenes, steroids, and polyphenols, including flavonoids in most of the tested extracts. The entire tested extracts showed moderate (512 μg/mL ≤ MIC ≤ 2048 μg/mL) to weak (MIC > 2048 μg/mL) antibacterial activities against the tested bacteria. Furthermore, extracts of leaf of Tristemma hirtum and pericarps of Raphia hookeri (at their MIC/2 and MIC/4) strongly potentiated the activities of all antibiotics used in the study, especially those of chloramphenicol (CHL), ciprofloxacin (CIP), kanamycin (KAN), and tetracycline (TET) against 70% (7/10) to 100% (10/10) of the tested MDR bacteria, with the modulating factors ranging from 2 to 128. The results of this study suggest that extracts from leaves of Tristemma hirtum and pericarps of Raphia hookeri can be sources of plant-derived products with antibiotic modifying activity.